2019
DOI: 10.1002/1873-3468.13372
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective C3‐substituent modification and substrate channeling by oxidoreductase BchC in bacteriochlorophyll a biosynthesis

Abstract: We report the in vitro activity of recombinant BchC oxidoreductase involved in bacteriochlorophyll a biosynthesis. BchC of Rhodobacter capsulatus preferentially oxidizes 31R‐3‐(1‐hydroxyethyl)‐chlorophyllide a and 31R‐3‐(1‐hydroxyethyl)‐bacteriochlorophyllide a in the presence of NAD+ to 3‐acetyl‐chlorophyllide a and bacteriochlorophyllide a, respectively, leaving the unreacted 31S‐epimers. In the reverse reaction, BchC with NADH predominately produces 31R‐epimeric alcohols from the 3‐acetyl‐(bacterio)chlorins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The pathway of BChl a biosynthesis in anoxygenic phototrophs is analogous to that of Chl a in oxygenic phototrophs up to the synthesis of Chlide a [15]. Following this, two additional modifications of Chlide a result in the production of BChlide a: (i) the C7 = C8 double bond of ring B is reduced by COR (BchXYZ) to produce 3-vinyl-BChlide a (3V-BChlide a) [70,71]; and (ii) 3V-BChlide a is converted to BChlide a by conversion of the C3 vinyl group to an acetyl group by the activities of 3V-BChlide hydratase (BchF) and BChlide dehydrogenase (BchC) [72][73][74]. Note that BchF and BchC may act before COR (producing 3-acetyl-Chlide a), as shown in figure 1.…”
Section: Synthesis Of Bacteriochlorophylls a B And G In Anoxygenic Ph...mentioning
confidence: 99%
“…The pathway of BChl a biosynthesis in anoxygenic phototrophs is analogous to that of Chl a in oxygenic phototrophs up to the synthesis of Chlide a [15]. Following this, two additional modifications of Chlide a result in the production of BChlide a: (i) the C7 = C8 double bond of ring B is reduced by COR (BchXYZ) to produce 3-vinyl-BChlide a (3V-BChlide a) [70,71]; and (ii) 3V-BChlide a is converted to BChlide a by conversion of the C3 vinyl group to an acetyl group by the activities of 3V-BChlide hydratase (BchF) and BChlide dehydrogenase (BchC) [72][73][74]. Note that BchF and BchC may act before COR (producing 3-acetyl-Chlide a), as shown in figure 1.…”
Section: Synthesis Of Bacteriochlorophylls a B And G In Anoxygenic Ph...mentioning
confidence: 99%
“…It was found at first that the cascade reaction experiments cannot be described well by using the cascade reaction model. Different explanations were found in the literature for this, such as molecular crowding and substrate channeling [31][32][33][34][35][36] which is quite common for the cascade reaction systems and the multi-enzyme reactions in general. Biochemists have been investigating substrate channelling for more than 30 years, but to synthetic chemists and biochemical engineers, this phenomenon is relatively unknown.…”
Section: The Mathematical Model Validation For the Cascade Reactionmentioning
confidence: 99%
“…33 Substrate channelling is explained as the phenomenon which enables the acceleration of the reaction catalysed by one enzyme in the presence of another enzyme. 31 This is explained with the formation of enzyme complexes which shorten the distance between the active sites of enzymes and due to that the diffusion limitation is overcome. 34 This phenomenon also affects the values of the kinetic constants 35,33 and can increase the stability of enzymes.…”
Section: The Mathematical Model Validation For the Cascade Reactionmentioning
confidence: 99%
“…Like in the CFE system, it was found that the model predicts the trends of the experimental data. However, it was necessary to re-estimate the maximum reaction rates (i.e., V m1 , V m2 , V m3 , V m4 ), considering the substrate channeling that occurs even easier within the cells. The re-estimated parameters are designated in SI (Tables S1 and S2).…”
Section: Results and Discussionmentioning
confidence: 99%